2010
DOI: 10.1002/mabi.201000352
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Polycaprolactone Scaffolds for Tissue Engineering of Annulus Fibrosus

Abstract: The annulus fibrosus comprises concentric lamellae that can be damaged due to intervertebral disc degeneration; to provide permanent repair of these acquired structural defects, one solution is to fabricate scaffolds that are designed to support the growth of annulus fibrosus cells. In this study, electrospun nanofibrous scaffolds of polycaprolactone are fabricated in random, aligned, and round-end configurations. Primary porcine annulus fibrosus cells are grown on the scaffolds and evaluated for attachment, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…Badylak et al, 1995;Dejardin et al, 2001;Jonsson et al, 2011;Kim et al, 2012;Kim et al, 2014b ; Ledet et al, 2009;Visage et al, 2006 Danhier et al, 2012;El-Amin et al, 2003;Endres et al, 2010;Feng et al, 2011;Kim et al, 2014a;Lai et al, 2014;Liang et al, 2013;Mizuno et al, 2004;Ruan et al, 2010 Poly-ε- Sinha et al, 2004;Silva et al, 2007;Li et al, 2005a;Lopez et al, 2010;Koepsell et al, 2011a ;Koepsell et al, 2011b;Martin et al, 2014 Martino et al, 2005). However, chitosan gels tend to be much softer and...…”
Section: Natural Solid Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Badylak et al, 1995;Dejardin et al, 2001;Jonsson et al, 2011;Kim et al, 2012;Kim et al, 2014b ; Ledet et al, 2009;Visage et al, 2006 Danhier et al, 2012;El-Amin et al, 2003;Endres et al, 2010;Feng et al, 2011;Kim et al, 2014a;Lai et al, 2014;Liang et al, 2013;Mizuno et al, 2004;Ruan et al, 2010 Poly-ε- Sinha et al, 2004;Silva et al, 2007;Li et al, 2005a;Lopez et al, 2010;Koepsell et al, 2011a ;Koepsell et al, 2011b;Martin et al, 2014 Martino et al, 2005). However, chitosan gels tend to be much softer and...…”
Section: Natural Solid Biomaterialsmentioning
confidence: 99%
“…PCL has currently undergone a resurgence in research for the purpose of controlled drug release (Agrawal and Ray, 2001;Dash and Konkimalla, 2012;Silva et al, 2007). PCL is interesting for regeneration of the AF because electrospun PCL fibres can mimic an AF fibre structural alignment (Koepsell et al, 2011b). It was shown that organised alignment by electrospinning induces ECM production by porcine AF cells on PCL scaffolds (Koepsell et al, 2011a).…”
Section: Poly(-ε-caprolactone)mentioning
confidence: 99%
“…Despite this, NP repair is likely to be insuicient, particularly in severely degenerate cases where tears in the AF may result in extrusion of the implanted biomaterial and/or cells; consequently a variety of studies have investigated biphasic scafolds which aim to repair the AF and NP simultaneously [118,125,126]. he use of electrospinning polymeric material has attracted signiicant interest in order to the replicate the highly organised native AF structure [127]. Lazebnik et al, (2011) used a biomimetic strategy by combining porcine chondrocyte cell seeded agarose gel surrounded by cell seeded electrospun polycaprolactine ibres and observed that cells were viable, well distributed and orientated themselves in the direction of the ibres [128].…”
Section: Cellular Biomaterials For Disc Degenerationmentioning
confidence: 99%
“…The mechanical tests revealed that POM has an excellent deformability: the compressive stress, young's modulus, and tensile strength markedly increased as the polymerization time increased. There was no permanent deformation after 500 press-loading and release cycles with Poly-D-L-lactide/Bioglass [90,91] Silk [92,93] Genipin crosslinked fibrin [94] Single unit with fiber orientation Aligned alginate/chitosan [88] Polycarbonate polyurethane linked with dihydroxyl oligomer [95,96] Polycaprolactone [97,98] Poly-L-Lactide [99] Silk fibers/chondroitin sulphate [100] Collagen fibrils [101] Biphasic scaffold Poly (polycaprolactone triol malate)/DBM [102] Composite scaffold Poly-L-Lactide as AF and hyaluronic acid hydrogel as NP [24] Polyglycolic Acid/poly-l-lactic as AF and alginate hydrogel as NP [103] Silk scaffold as AF and silicon as NP or hyaluronic acid as NP [104,105] 30 % maximum strain. When implanted into mice back subcutaneous pocket, there were no inflammation responses were found [89].…”
Section: Single Unit Without Fiber Orientationmentioning
confidence: 99%
“…Other electrospun nanofibrous scaffolds such as polycaprolactone were fabricated in random, aligned, and round-end configurations [97]. A modified electrospinning technique was utilized to generate aligned nanofibrous polymer scaffolds for engineering the basic functional unit of the AF, a single lamella [98].…”
Section: Single Unit With Oriented Fibermentioning
confidence: 99%